Local drug delivery systems for treating periodontal diseases (A review of literature) - Taresh, Adnan K; Juma, Saif S S (Journal of Baghdad College of Dentistry, 2013)
In this review of literature, the light will be concentrated on the local drugs delivery systems for treating the periodontal diseases. Principles, types, advantages and indications of each type will be discussed in this paper.